Heterodimer formed by ROC8 and ROC5 modulates leaf rolling in rice. Issue 12 (8th September 2021) - Xu, Yang; Kong, Weiyi; Wang, Fangquan; Wang, Jun; Tao, Yajun; Li, Wenqi; Chen, Zhihui; Fan, Fangjun; Jiang, Yanjie; Zhu, Qian‐Hao; Yang, Jie
Summary: Moderately rolled leaf is one of the target traits of the ideal plant architecture in rice breeding. Many genes, including homeodomain leucine zipper IV transcription factors ROC5 and ROC8, regulating rice leaf rolling have been cloned and functionally analysed. However, the molecular mechanism by which these genes modulate leaf‐rolling remains largely elusive. In this study, we demonstrated the transcription activation activity of both ROC8 and ROC5. Overexpressing ROC8 caused adaxially rolled leaves due to decreased number and size of bulliform cells, whereas knockout of ROC8 induced abaxially rolled leaves due to increased number and size of bulliform cells. ROC8 and ROC5 each could form homodimer, but ROC8 interacted preferably with ROC5 to forms a heterodimer. Importantly, we showed that the ROC8‐ROC5 heterodimer rather than the homodimer of ROC8 or ROC5 was functional as neither overexpressing ROC8 in the ROC5 mutant nor overexpressing ROC5 in the ROC8 ‐knockout line could rescue the mutant phenotype. This was further partially supported by the identification of a large number of common differentially expressed genes in single and double mutants of roc8 and roc5 . ROC8 and ROC5 were functionally additive as the phenotype of abaxially rolled leaves was stronger in the roc5roc8 double mutant than in their single mutants. Our results provide evidence for the role of dimerization of ROC members in regulating leaf rolling of rice.